A Comparative Study on Financial Performance of HDFC Bank Ltd and ICICI Bank - Juikar, Kavita; Verma, Deepak (Journal of Neonatal Surgery, 2025)
Financial performance of the bank always useful criteria to attract prospective customers. Financial performance creates confidence in the minds of customers. Financial analysis is a good criterion for understanding the performance and financial stability of a bank. For the present comparative study HDFC Bank and ICICI Banks has been selected and their financial statement for the last 3 years have been used. The researcher used ratio analysis to try to find out which bank is most efficient in achieving its goals. To find out actual performance of bank capital adequacy ratio, non-performing asset ratio, fixed asset turnover ratio, Gross Profit Ratio, Net profit Ratio, current Ratio was used.